Imagining novel landscape approaches for territorial development in the Mediterranean (and beyond) - Muñoz-Rojas Morenés, José (2018)
The Ecosystem Services framework is widely acknowledged as a useful tool to facilitate the economic valuation of ecological resources and to support their role as key assets for territorial sustainable development. Consequently, it is a considered as an effective framework to design and implement sustainable land-use decisions. However, critiques and limitations are rapidly arising in land-use science and governance. These limitations are especially evident for territories where human history and culture are considered as co-substantial with ecological processes in shaping sustainable and resilient land-use systems and landscapes. A clear example of this are Mediterranean regions, where highly valued land-use systems exist on which nature and culture cannot be easily disentangled in their importance as drivers of sustainability. We argue that this is a geographical context where landscapes can be considered as more relevant than ecosystems for sustainable territorial development. This argument is based on the definition of landscapes as complex spatial constructs resulting from the interplay between multiple human actions and perceptions of the territory. This includes the inherent recognition that is made within the concept of landscape of the complexity of human-nature relationships, turning landscapes more apt to imagine innovative and sustainable land-use and territorial pathways for culturally rich territories than those potentially provided by ecosystem services. In this paper, we will explore the advantages of landscape approaches for sustainable territorial development compared to ecosystem services focusing in Mediterranean areas. Potential advantages to be explored include the capacity of landscape approaches to bridge together the territorial, spatial and socio-cultural aspects of land-use decision making, the potentialities raised through landscape services to resolve problems in the operationalization of cultural ecosystem services, and the inherent capacity of the concept of landscape to underpin integrated territorial governance frameworks that help resolve the many problems with traditional silo land-use policies and related administrative structures. To test these issues, two case studies (Montado multi-functionality vs Olive crop intensification) were examined in the Alentejo (Portugal) that represent extremes in the wide range of land-use trajectories encountered throughout the Mediterranean region. Our findings show how a landscape-based approach to territorial governance can enrich the current debate about alternative options (e.g. intensification vs extensification, land-sharing vs land-sparing, multi-functionality vs specialization) for sustainable land-use change. Furthermore, we argue that these ideas can be tested in other cases and regions beyond the Mediterranean, where culture and nature jointly shape the character and value of their landscapes and territories.